An exploration of the nature of therapeutic nursing in a general rehabilitation team : a thesis presented in partial fulfilment of the requirements for the degree of Master of Arts in Nursing at Massey University - Price, Eileen (Massey University, 1997)
The role of the nurse in the rehabilitation specialty has been defined in terms of the tasks and functions which nurses perform. Whilst the therapeutic contribution of other disciplines is more clearly understood, the extent to which nursing activities are therapeutic is not clear. Therapy is defined as activity which brings about healing or an improved outcome for the customer and is arguably the raison d'être of the rehabilitation specialty. The purpose of this study was to explore the concept of therapeutic nursing in a rehabilitation context from the perspective of the nurse and the customer. The purpose was not to explore all aspects of nursing activity. This was neither within the scope of the study nor necessarily consistent with the research question. The aim was to make more transparent to nurses and to their colleagues just what constitutes the therapeutic work of nursing in rehabilitation, enabling nurses to focus specifically on activity which is of a therapeutic nature and consequently offer nursing which is specifically rehabilitative. The investigator was the Team Leader of a General Rehabilitation Team in a rehabilitation unit located in a major city in New Zealand. The study design used the Focus Group method to collect data from nurse participants in the team. Thematic analysis applied to the data generated nurse-validated categories of therapeutic activity. Also, during the study discharged customer participants were invited to answer a questionnaire about their perceptions of the nature of therapeutic nursing activity. The responses facilitated a comparison between nurse and customer perceptions of therapeutic nursing. Major themes were extracted from the data and there was congruency between nurse and customer data. Together these themes created a profile of the nurse as a coach. This role constitutes a leadership role in the team, with the customer and with the family. Coaching activity supports the customer through the rehabilitation programme, assists in overcoming barriers to progress and creates opportunities to develop independence. A new model for rehabilitation nursing practice is proposed, and recommendations for practice, research and education are described.
Keywords: Rehabilitation nursing; Nurse and patient